37th Structure, Structural Dynamics and Materials Conference 1996
DOI: 10.2514/6.1996-1545
|View full text |Cite
|
Sign up to set email alerts
|

Forced response of mistuned bladed disks using reduced-order modeling

Abstract: A reduced-order model formulation is presented for examining the forced response of tuned and mistuned bladed disks. The technique developed uses modal information obtained from highly detailed FEM models to create, in a systematic manner, much simpler and computationally inexpensive models of bladed disks. The small size of the reduced-order model and associated computational savings enable analysts to examine the effect of mistuning strength and pattern, interblade coupling, and localized modes on forced res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Figure 2 shows the occurrence of numerous natural frequency veering regions. Earlier studies [18,31] have shown that large increases in the mistuned forced response, relative to the tuned response, are likely to occur in veering regions. Therefore, the ability of CMM models to capture the mistuned response in veering regions was tested, and two such regions were investigated: veering region 1 is located at three nodal diameters, around 28 kHz; and veering region 2 is located at five nodal diameters, around 34 kHz.…”
Section: Small Mistuning Case Studymentioning
confidence: 97%
See 2 more Smart Citations
“…Figure 2 shows the occurrence of numerous natural frequency veering regions. Earlier studies [18,31] have shown that large increases in the mistuned forced response, relative to the tuned response, are likely to occur in veering regions. Therefore, the ability of CMM models to capture the mistuned response in veering regions was tested, and two such regions were investigated: veering region 1 is located at three nodal diameters, around 28 kHz; and veering region 2 is located at five nodal diameters, around 34 kHz.…”
Section: Small Mistuning Case Studymentioning
confidence: 97%
“…As mentioned earlier, there are two blade-dominated mode groups in this range. In all four cases, 136 tuned-system normal modes (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) were used as a basis, but mistuning projections were performed differently. In Fig.…”
Section: Nonproportional Mistuningmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology has intensively been studied in the framework of the linear dynamic analysis (see for instance, [4,5,6,7,8,9,10,11,12,13,14]), for which the mistuning effects have been modeled using either parametric probabilistic approaches (see for instance, [15,16,17,18,19]), or using the nonparametric probabilistic approach ( [20,21,22]), and for which the optimization of alternating patterns has been studied (see for instance, [23,24,25,26]).…”
Section: Introductionmentioning
confidence: 99%
“…Different reduced-order modeling techniques have been developed to compute the dynamic behavior of mistuned bladed disks with reduced computational time [2,3,4,5,6,7,8,9,10,11,12,13,14]. These finite element model of the structures.…”
Section: Introductionmentioning
confidence: 99%